SOCIAL MEDIA AND WHISTLEBLOWING - Bambang Arianto (Universitas Airlangga, 2021)
This article elaborates on the role of social media as a whistleblowing channel used to detect fraudulent practices. The increasing use of social media in various life activities has made social media turn into a channel for the exchange and dissemination of civic information. This article elaborates on the use of social media as an alternative channel for whistleblowing in addition to the use of other anonymous channels. So far, the whistleblowing system has been created only through integrated means such as websites and special applications. The active participation of netizens means that social media can be used by whistleblowers to report various indications of fraudulent practices (fraud). This study used an explanatory qualitative method with data collection techniques through in-depth interviews (in-dept interview).This article states that social media has contributed positively as a whistleblowing channel in an effort to detect various fraudulent practices in all entities and the public sector.